Pre–T Cell Receptor (Tcr) and Tcr-Controlled Checkpoints in T Cell Differentiation Are Set by Ikaros - Winandy, Susan (The Rockefeller University Press, 1999)
T cell differentiation relies on pre–T cell receptor (TCR) and TCR signaling events that take place at successive steps of the pathway. Here, we show that two of these T cell differentiation checkpoints are regulated by Ikaros. In the absence of Ikaros, double negative thymocytes can differentiate to the double positive stage without expression of a pre-TCR complex. Subsequent events in T cell development mediated by TCR involving transition from the double positive to the single positive stage are also regulated by Ikaros. Nonetheless, in Ikaros-deficient thymocytes, the requirement of pre-TCR expression for expansion of immature thymocytes as they progress to the double positive stage is still maintained, and the T cell malignancies that invariably arise in the thymus of Ikaros-deficient mice are dependent on either pre-TCR or TCR signaling. We conclude that Ikaros regulates T cell differentiation, selection, and homeostasis by providing signaling thresholds for pre-TCR and TCR.